2005
DOI: 10.1152/ajpcell.00259.2004
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for membrane depolarization in epithelial wound healing

Abstract: Chifflet, Silvia, Julio A. Herná ndez, and Silvina Grasso. A possible role for membrane depolarization in epithelial wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
107
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 63 publications
11
107
0
Order By: Relevance
“…Previous studies have shown that VSMC migration, from the media into the intima, plays a significant role following arterial injury, and blocking VSMC migration can reduce the neointimal lesion size (Rutherford et al, 1997;Slepian et al, 1998). A role for DEG/ ENaC/ASIC proteins in cellular migration has been suggested in recent reports (Chifflet et al, 2005;Grifoni et al, 2006;Vila-Carriles et al, 2006). Our previous study showed that DEG/ ENaC/ASIC pharmacological inhibition with amiloride and its analog benzamil inhibit VSMC migration.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that VSMC migration, from the media into the intima, plays a significant role following arterial injury, and blocking VSMC migration can reduce the neointimal lesion size (Rutherford et al, 1997;Slepian et al, 1998). A role for DEG/ ENaC/ASIC proteins in cellular migration has been suggested in recent reports (Chifflet et al, 2005;Grifoni et al, 2006;Vila-Carriles et al, 2006). Our previous study showed that DEG/ ENaC/ASIC pharmacological inhibition with amiloride and its analog benzamil inhibit VSMC migration.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, others and we have shown members of the Degenerin/Epithelial Sodium (Na + ) Channel/Acid Sensing-Ion Channel (DEG/ENaC/ASIC) protein family, contribute to cellular migration in glial, epithelial and VSM cells (Chifflet et al, 2005;Grifoni et al, 2006;VilaCarriles et al, 2006). Members of this family share a similar structure, two membrane spanning domains separated by a large extracellular domain and intracellular N-and C-termini.…”
Section: Introductionmentioning
confidence: 99%
“…However, PcTX-1 prevented a regulatory volume increase in glioma cells following a hyperosmotic challenge (19). It has previously been suggested that in addition ENaC plays an important role in wound healing (33,34) and proliferation (35). Both ASIC and ENaC channels contribute to migration of vascular smooth muscle cells (36,37), although in neither case are the underlying mechanisms well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature reports that different mammalian cell types possess different degrees of well-defined V mem states. Hence, the V mem state might be a cellspecific marker in many cases, such as in proliferative (Binggeli and Weinstein, 1986;Marino et al, 1994) V mem acts in olfactory nerve regeneration of the tiger salamander (Masukawa et al, 1985), in development (Hotary and Robinson, 1994) and leftright asymmetry (Adams et al, 2006) of Xenopus embryos, in Xenopus tail regeneration (Adams et al, 2007), in epithelial wound healing of bovine cornea (Chifflet et al, 2005), in autocrine activation of two-cell mouse embryos (Li et al, 2007), K þ channel expression and proliferation of oligodendrocyte progenitor cells (Knutson et al, 1997), and adherens junctions and reorganization of the actin cytoskeleton in bovine corneal endothelial cells (Nin et al, 2009). Consistent with studies in Xenopus (Adams et al, 2007), we found that V mem shows a significant degree of depolarization, especially at 6 hpa (five-fold) in the regeneration bud vs. uncut tail in axolotl embryos.…”
Section: Memmentioning
confidence: 99%